THE ROLE OF IDIOMS IN COMMUNICATION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation: Language is not just a means for transmitting simple information; it is a sophisticated form of communication that enables us to convey feelings, exchange cultural subtleties, and interact on levels that extend beyond the surface definition of words. One of the most intriguing features of language is the utilization of idioms - expressions whose meanings are not directly related to the words used, but rather are grasped culturally and contextually. Idioms, whether we are aware of it or not, are crucial in communication, enhancing our conversations and allowing us to connect with others on a deeper level. In this article, we investigate the importance of idioms in communication, how they enrich our language, and why we frequently rely on them in daily discussions.